Use of Flame Color and Chemiluminescence for Early Detection of Lean Blowout in Gas Turbine Combustors at Different Levels of Fuel–Air Premixing. Issue 5 (3rd May 2020) - De, Somnath; Biswas, Ankit; Bhattacharya, Arijit; Mukhopadhyay, Achintya; Sen, Swarnendu
ABSTRACT: Lean combustion is adopted in the practical gas turbine combustors as it offers a solution to reduce the emission of NO x . But lean blowout (LBO) is considered as the main threat in taking the ultra-lean premixed combustion. LBO can also occur in aircraft engines during rapid decrease in speed or power. Although gas turbine flames can be of both premixed and partially premixed in nature, early detection of LBO of partially premixed flames has received relatively less attention compared to premixed flames. In this paper, attention has been focused on the early detection of LBO in combustors with different levels of premixing. Apart from that, a detail investigation on the electromagnetic emission of the flame is performed in order to have the insight of the dominating chemiluminescence. The primary chemiluminescence species, OH*, CH *, and C2 *, are considered in this study. The flame dynamics is captured using spectral signal obtained from a spectrometer. Also, the spectrums of different colors, emitted by the flame at different conditions, are studied using both spectrometer and color Charge Coupled Device (CCD) camera. At lean condition of the premixed flame, three narrowband emissions in the visible (VIS) range, namely, blue, violet, and indigo colors, are observed. Three primary parameters, α, β, and γ, are introduced based on the color ratios when numerator of the ratio is the intensity of red band. Near LBO, each of these parameters becomes significantly low. The observation range for this analysis is considered from stoichiometric condition to the extreme lean region, where LBO occurs. At the end, the behavior of the red, green, and blue color ratios toward the LBO using both camera and spectrometer is compared. The similarity between the results of camera and spectrometer indicates that flame imaging through commercial color CCD camera can provide a low cost, simple tool for LBO detection.